ANALISIS STRATEGI MANAJEMEN KINERJA DALAM MENILAI DAN MENINGKATKAN PRODUKTIVITAS KARYAWAN: KAJIAN PUSTAKA TENTANG PENDEKATAN EVALUATIF, MOTIVASI, DAN PENGEMBANGAN KOMPETENSI DI LINGKUNGAN ORGANISASI MODERN - Ignatius Septo Pramesworo; Tehedi Tehedi (Adiba Aisha Amira, 2025)
This study aims to analyse performance management strategies in assessing and improving employee productivity. In a dynamic and competitive modern organisational environment, performance management not only functions as an administrative control tool but has evolved into a strategic system oriented towards optimising human resource potential. Through a literature review method, this study examines various academic literature and relevant empirical research results to identify the relationship between performance evaluation systems, work motivation, and competency development on productivity improvement. The results of the study indicate that an evaluative approach that is objective, evidence-based, and accompanied by continuous feedback can strengthen employee responsibility and engagement. Furthermore, motivation and competency development strategies have been proven to have a significant effect in creating positive work behaviour, improving skills, and forming an adaptive organisational culture. The integration of these three approaches forms a comprehensive, effective, and sustainable strategic performance management framework, which ultimately supports increased productivity and organisational competitive advantage in the era of digital transformation.